Getting critical thinking about ecosystem: How impact and responses of students about the CirGi learning model? - Harahap, Lia Junita; Ristanto, Rizhal Hendi; Komala, Ratna (Biosfer: Jurnal Pendidikan Biologi, 2020)
The broad scope of biology and the many sources of biology reading requires eleven grade students to think critically about sorting out information to develop and support students' critical thinking skills. CirGi is an integration of the cooperative integrated reading and composition (CIRC) learning model and guided inquiry (GI) that emphasizes reading and writing activities, accompanied by guidance from the teacher. This study aimed to analyze the influence of CirGi's learning model on students' critical thinking skills. This research uses a quasi-experiment method with pre-post control group design. The sampling technique used purposive sampling, namely 104 high school students. Data collection was carried out using instruments of critical thinking skills in the form of essays, questionnaire responses of students to learning, and observation sheets of syntax implementation. The data analysis technique used was one-way ANCOVA. After controlling for the pretest scores, the CirGi learning model's influence on students' critical thinking skills was influenced. This learning model was appropriate for learning biology, so it can regrow the activities of reading science books that impact students' critical thinking skills.